PENDIDIKAN BERKELANJUTAN DALAM PERSPEKTIF GLOBAL: ANALISIS LITERATUR TENTANG IMPLEMENTASI TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) DI SEKOLAH DASAR - Siva Salsabila; Heri Effendi; Wirnita; Yulia Arnita; Kasih Munikza; Dea Leski Sholeha; Cinta Putri (STKIP Subang, 2026)
The implementation of the Sustainable Development Goals (SDGs) in primary education is a strategic effort to build the foundation for a sustainable future through quality, inclusive, and equitable education. This study aims to analyze the implementation of SDGs in primary schools through a literature review of various national and international journal articles, policy documents, and research reports published between 2020 and 2025. This research uses a qualitative approach with a systematic literature review method, involving the stages of identification, screening, feasibility assessment, and data synthesis from 16 relevant sources. The analysis results show that SDGs implementation in primary schools is carried out through integration into the Merdeka Curriculum, the RADEC learning model oriented toward Education for Sustainable Development (ESD), and Adiwiyata school programs. Key challenges identified include the digital divide between urban and rural areas, limited teacher competence, and low parental involvement. The findings indicate that the synergy between the Merdeka Curriculum, ESD-oriented pedagogy, and community involvement is key to the success of sustainable education. This study recommends strengthening continuous professional development for teachers, equitable distribution of educational infrastructure, and increasing parental and community participation in SDGs-based learning programs.